Yeast FIT2 homologs mediate the crosstalk between stress response pathways and cellular proteostasis - Teng, Peter Shyu Jr. (2019)
Lipid droplets (LDs) have long been regarded as inert cytoplasmic organelles with the primary function of housing excess intracellular lipids. More recently, LDs have been strongly implicated in conditions of lipid and protein dysregulation. Moreover, these conditions are major contributors to the pathophysiology of metabolic diseases and concomitantly activate cellular stress response pathways, namely the unfolded protein response (UPR) and heat shock response (HSR). However, despite the increasing support for the involvement of LDs in other cellular processes, mechanistic insight into the fundamental process of LD biogenesis and its direct physiological relevance to the cell remains rudimentary. The fat storage inducing transmembrane (FIT) family of proteins comprises of evolutionarily conserved endoplasmic reticulum (ER)-resident proteins that have been reported to induce LD formation. Using Saccharomyces cerevisiae as a model, this study aims to dissect the role of LDs in cellular lipid and protein homeostasis through the yeast FIT homologs (ScFIT), SCS3 and YFT2. While LD biogenesis and basal UPR activation remain unaltered in ScFIT mutants, SCS3 was found to be essential for proper stress-induced UPR activation and for viability in the absence of the sole yeast UPR sensor IRE1. Devoid of a functional UPR, scs3Δ mutants exhibited accumulation of triacylglycerol within the ER along with aberrant membrane morphology, indicative of impaired ER-LD lipid partitioning and suggesting a UPR-dependent compensatory mechanism for LD maturation. Surprisingly, the absence of the ScFIT proteins results in the downregulation of the closely-related HSR pathway. In line with this observation, global protein ubiquitination and the turnover of both ER and cytoplasmic misfolded proteins is impaired in ScFITΔ cells, while a screen for interacting partners of Scs3 identifies components of the proteostatic machinery as putative targets. Taken together, these suggest that ScFITs may modulate proteostasis and stress response pathways with lipid metabolism at the interface between the two cellular processes.